Commodity risk assessment of Fagus sylvatica plants from the UK - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Alan MacLeod; Christer Sven Magnusson; Panagiotis Milonas; Juan A Navas‐Cortes; Stephen Parnell; et al. (EFSA Journal)
Abstract The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in Commission Implementing Regulation (EU) 2018/2019 as ‘High risk plants, plant products and other objects’. This Scientific Opinion covers plant health risks posed by plants of Fagus sylvatica imported from the United Kingdom (UK) as: (a) 1‐ to 7‐year‐old bare root plants for planting, (b) < 1‐ to 15‐year‐old plants in pots and (c) bundles of 1‐ to 2‐year‐old whips and seedlings, taking into account the available scientific information, including the technical information provided by the UK. All pests associated with the commodity were evaluated against specific criteria for their relevance for this opinion. Two EU quarantine pests, Phytophthora ramorum (non‐EU isolates) and Thaumetopoea processionea, and two pests not regulated in the EU, Meloidogyne mali and Phytophthora kernoviae, fulfilled all relevant criteria and were selected for further evaluation. For the selected pests, the risk mitigation measures implemented in the technical dossier from the UK were evaluated taking into account the possible limiting factors. For these pests an expert judgement is given on the likelihood of pest freedom taking into consideration the risk mitigation measures acting on the pest, including uncertainties associated with the assessment. In the assessment of risk, the age of the plants was considered, reasoning that older trees are more likely to be infested mainly due to longer exposure time and larger size. The degree of pest freedom varies among the pests evaluated, with M. mali being the pest most frequently expected on the imported plants. The expert knowledge elicitation (EKE) indicated with 95% certainty that between 9,793 and 10,000 plants in pots up to 15 years old per 10,000 will be free from M. mali.